Editorial Board and Guideline for the Authors, SOSIOHUMANIKA Journal, Issue of November 2015 - SOSIOHUMANIKA, Editor Journal (SOSIOHUMANIKA, 2015)
SOSIOHUMANIKA will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment, and analysis on the key issues surrounding the humanities and social sciences education and its various aspects. Analysis will be practical and rigorous in nature.Surabaya, Indonesia: November 2015.Â Dr. M. SubandowoVice Chief Editor of the SOSIOHUMANIKA Journal in Bandung, West Java; and Senior Lecturer at the Graduate Program UNIPA (University of PGRI Adibuana) in Surabaya, East Java, Indonesia.Â